Application of Assaf panel for evaluating throwing power of pulse reverse electroplating on complex geometries. (3rd September 2018) - Leisner, P.; Zanella, C.
ABSTRACT: The Assaf panel arrangement was used for evaluating pulse reverse plating processes and optimisation of the throwing power (TP) of complex three-dimensional (3D) geometries. Two different electroplating processes were investigated: an acid copper bath and a cyanide silver bath without additives. It has not been possible to establish a direct correlation factor for TP obtained with the Assaf panel and the 3D objects included in the trials. Nevertheless, the Assaf panel was found to be a useful tool for preliminary process parameter optimisation. The copper bath needs agitation to deposit coatings of good quality, whereas the silver bath obtains the best throwing power without agitation. The latter is probably due to inhibition by adsorbed cyanide.